2018
DOI: 10.3389/fpsyg.2018.01036
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization and Aggressive Behavior Among Chinese Adolescents: Delinquent Peer Affiliation as a Mediator and Parental Knowledge as a Moderator

Abstract: Grounded in social network theory and a risk-buffering model, this study examined whether delinquent peer affiliation mediated the association between peer victimization and adolescent aggressive behavior and whether this mediating process was moderated by parental knowledge. A total of 4,209 Chinese adolescents (48.47% male, Mage = 13.68) completed questionnaires on peer victimization, parental knowledge, delinquent peer affiliation, and adolescent aggressive behavior. Path analyses showed that delinquent pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 47 publications
3
36
0
3
Order By: Relevance
“…The Cronbach’s alpha was 0.86 for this questionnaire in this study. In Chinese adolescents, this questionnaire demonstrated good validity and reliability [ 29 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Cronbach’s alpha was 0.86 for this questionnaire in this study. In Chinese adolescents, this questionnaire demonstrated good validity and reliability [ 29 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…School victimization is defined as a type of peer abuse in which students are subjected to violent verbal, physical, and psychological behavior by one or more peers [1,2]. This problem has serious consequences for the development and psychosocial adjustment of students [3][4][5]. As regards gender, data suggest that, in the case of school victimization, boys are victimized by their partners overtly and girls relationally [6,7], although some studies have not reported such differences [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Participants reported on their own aggressive behaviors using the Chinese version of the Buss–Warren aggression questionnaire (BWAQ) (Maxwell, 2008; Lin et al, 2018). In the current study, 19 items were used indicating levels of physical, relationship, and verbal aggression behaviors during the past 6 months, such as “Once in a while, I can’t control the urge to strike another person.” Responses are rated on a 5-point scale (from 1 = Not at all to 5 = Absolutely like me ).…”
Section: Methodsmentioning
confidence: 99%
“…During adolescence, time spent with family steadily decreases and an increasing amount of time is spent in the company of peers (Zhu et al, 2016; Lin et al, 2018; Tian et al, 2019). Prior research has repeatedly shown that affiliate with deviant peers plays an important role in shaping adolescent problem behaviors including aggressive behavior (Longobardi et al, 2017; Zhu et al, 2017; Lin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation